Employment Status as Dominant Predictive Factor of Early Breastfeeding Cessation - Siska Ningtyas Prabasari; Risa, Istiqomah; Riyanti, Rita; Triani, Yuyun (Gaster, 2025)
Background: Early cessation of breastfeeding is a significant health problem, considering that exclusive breastfeeding has been proven to provide important benefits for the health of mother and child. Risk factors such as maternal factors including age, education level, employment status, family income, parity, and mode of delivery contribute to the decision to stop breastfeeding early. Purpose: This study aimed to identify dominant factors that contribute to early cessation of breastfeeding Method: This study applied a cross-sectional design. 30 breastfeeding mothers who exclusively breastfeed after giving birth up to six months were selected as respondents through purposive sampling technique. Respondents were then asked to fill out the questionnaire of the Breastfeeding Attrition Prediction tool (BPAT) to identify early breastfeeding cessation. Data analysis was performed using univariate, bivariate, and multivariate methods using chi-square and logistic regression. Result: The study clearly shows that parity, employment status, and mode of delivery are significantly linked to each other with early breastfeeding cessation (p < 0.05). Employment status is the most influential factor in early breastfeeding cessation, p-value 0.000 (OR=14.34; CI 95% 6.7–32.4). Conclusion: Employment status was the dominant predictive factor that has the potential for early breastfeeding cessation. Working mothers are more likely to opt for early weaning due to time constraints, workplace challenges, and fatigue.